CONCENTRATION OF INVESTMENT CAPITAL IN MERGERS AND ACQUISITIONS: PREREQ-UISIGTES FOR A TECHNOLOGICAL BREAKTHROUGH (INNOVATIVE ECONOMY, 2024)
Bagatska K.V., Korbutiak A.H. CONCENTRATION OF INVESTMENT CAPITAL IN MERGERS AND ACQUISITIONS: PREREQUISIGTES FOR A TECHNOLOGICAL BREAKTHROUGHPurpose. The purpose of the article is to substantiate the prerequisites for systemic economic shifts based on the analysis of the structure of capital investments and mergers and acquisitions.Methodology of research. General scientific and special methods were used in the course of the study, in particular, analysis, synthesis, and generalization were applied while working with statistical data on the mergers and acquisitions market, and the monographic method was used when studying literary sources on issues related to the research topic. Financial analysis techniques (specifically, ratio and horizontal analysis) were used in assessing the structure of capital investments in various sectors of the economy over the past twelve years (up to 2022). Additionally, the analysis of structural changes and shifts, as well as methods of comparison and graphical analysis, were employed to study the dynamics of structural shifts in the economy under the influence of investment capital movement.Findings. The study of the preconditions for structural economic transformations was conducted through the assessment of the dynamics of investment capital concentration in economic sectors and the analysis of the dynamics of the number and value of mergers and acquisitions in pre-war and wartime periods, as well as a review of the motives behind these transactions. The preconditions for structural changes in the economy, which are being laid at this stage through the investment decisions of investors and the political decisions of government representatives, were analyzed. The conducted research indicates the need to maintain a high share of industrial capital concentration alongside the decline in the share of industry in GDP due to the substantiated necessity for significant modernization of certain sectors.Originality. The study for the first time highlighted the role of investment capital by analysing the dominance of progressive industries with high added value in the structure of mergers and acquisitions, which can become the beginning of the structural transformation of the Ukrainian economy with the concentration of investment capital in high-income sectors. The use of analysis of the structure of capital investments by economic sectors has further developed as a tool for determining the investment attractiveness of individual sectors and the dynamics of changes in the investment preferences of entities.Practical value. The results of the study can be used by government bodies in the development and refinement of the country's investment strategy, the formulation of the principles of the state's investment policy, and the adjustment of existing plans for post-war recovery; by private companies and investors (both local and foreign) for developing plans for the analysis and investment in Ukrainian economic assets, adjusting their expectations and priorities; by members of the scientific community who are interested in further development of this research topic; and by experts in related disciplines to expand their understanding of the issue, which may be relevant to their area of expertise, among others.Key words: investments, capital investments, capital concentration, capital market, mergers and acquisitions.
Keywords: investments; capital investments; capital concentration; capital market; mergers and acquisitions.